Diagnostic value of diffusion-weighted imaging on sporadic Creutzfeldt-Jakob disease - Yan-hui YANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2014)
Objective To explore the diagnostic value of diffusion-weighted imaging (DWI) on sporadic Creutzfeldt-Jakob disease (sCJD).  Methods The MRI findings of 21 patients with clinically proved probable sCJD were analyzed retrospectively and the characteristics were summarized especially in DWI.  Results 1) All 21 cases of sCJD were shown abnormal in DWI, which appeared as linear hyperintensity signals in cerebral cortex and patchy hyperintensity in caudate nucleus and (or) lenticular nucleus. 2) The abnormal signals were most commonly seen in cerebral cortex accompanied with the basal ganglia (16 cases, 76.19%). Besides, there were 3 cases of cortex involvement (14.29%) and 2 cases of basal ganglia involvement (9.52% ). Among the lesions in cerebral cortex, the frontal and parietal lobes were affected more commonly (15 cases, 78.95%; 13 cases, 68.42%) than the temporal and occipital lobes (12 cases, 63.16%; 9 cases, 47.37%). 3) DWI was superior to T1WI, T2WI and FLAIR imaging sequences. The abnormal signals in DWI were accompanied by decreased apparent diffusion coefficient (ADC) values. 4) During the follow-up in 5 patients, the range and intensity of high signal changed in DWI, and only one case presented reduced range of abnormal signal. Conclusions sCJD manifests characteristic changes on DWI, which should be suggested as an essential tool for diagnosing sCJD.   doi: 10.3969/j.issn.1672-6731.2014.04.010